Regulatory Mechanism on Anti-Glycolytic and Anti-Metastatic Activities Induced by Strobilanthes crispus in Breast Cancer, In Vitro - Siti Nur Hasyila Muhammad; Nur Arnida Mohd Safuwan; Nik Soriani Yaacob; Agustine Nengsih Fauzi (MDPI AG, 2023)
An active fraction of S. crispus, F3, and its bioactive compounds (lutein, β-sitosterol, and stigmasterol) were reported to have anti-glycolytic activities in MDA-MB-231 cells. Since glycolysis can also regulate metastatic activities in cancer cells, this study investigated the mechanism underlying the anti-glycolytic and anti-metastatic activities induced by F3 and its bioactive compounds on MDA-MB-231 cells. The cells were treated with IC50 concentrations of F3, lutein, β-sitosterol, and stigmasterol. GLUT1 protein expression and localization were then observed using a fluorescence microscope. We found that F3, lutein, and β-sitosterol inhibit localization of GLUT1 to the cell membrane, which causes the decrease in glucose uptake. This is supported by a reduction in PKC activity, measured using a spectrophotometer, and increased TXNIP protein expression detected by Western blotting. Both TXNIP and PKC are involved in GLUT1 activation and localization. The expression of signaling proteins involved in the PI3K/AKT pathway was also measured using a flow cytometer. Results show that F3, lutein, β-sitosterol, and stigmasterol reduced the expression of AKT, pAKT, mTOR, and HIF1α in MDA-MB-231 cells. Transwell migration assay was used to measure migration of the MDA-MB-231 cells. A reduction in fibronectin protein expression was observed by fluorescence microscopy, after treatments with F3 and its bioactive compounds, leading to a reduction in the MDA-MB-231 cells' migratory abilities. As a conclusion, F3 acts as a metabolic inhibitor by inhibiting metabolic rewiring in the promotion of cancer metastasis, potentially due to the presence of its bioactive compounds.